Diversity as a social value and object of protection in Polish penal law - Bek, Dominika (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2026)
The article deals with Polish constitutional and penal law issues centred around the question of whether social diversity is an object of protection under penal law. The article defines diversity, including social diversity, before examining views on its social value in different areas and contexts, including from ontological and legal perspectives. In presenting a spectrum of approaches to diversity, it uses the example of social and political reactions to the multitude of cultures (multiculturalism). The recognition of the value of diversity makes it possible to identify manifestations of its protection in the Polish Constitution. The Constitution treats primarily national and ethnic diversity, as well as religious and worldview diversity, as a legal good. The Penal Code turns out to be axiologically consistent with the Constitution. The analysed individual types of prohibited acts may be identified as protecting mainly manifestations of cultural differentiation (including national, ethnic, racial and religious diversity). To a narrower extent and indirectly, the law also protects diversity in other respects by protecting freedom to choose one’s conduct. The article also discusses manifestations of social diversity that are directly criminalized, such as bigamy, forced marriage, and female genital mutilation. The article takes into account the Act of 6 March 2025 amending the Penal Code in relation to so-called hate crimes and expanding the scope of diversity protection in penal law to include disability, age, gender, and sexual orientation. However, the Act was deemed unconstitutional.